2002
DOI: 10.1042/bj20011848
|View full text |Cite
|
Sign up to set email alerts
|

Events in the immortalizing process of primary human mammary epithelial cells by the catalytic subunit of human telomerase

Abstract: The in vitro immortalization of primary human mammary epithelial (HME) cells solely by the exogenous introduction of the catalytic subunit of human telomerase (hTERT) has been achieved. Early passage hTERT-transfected HME (T-HME) cells continuously decreased the length and density of telomeres even in the presence of telomerase activity, with a significant number of cells staining positive for senescence-associated beta-galactosidase (SA-beta-gal). Subsequently, with the increase in cell passages, the copy num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…INK4a pathway is inactivated (Kiyono et al, 1998;Farwell et al, 2000;Kim et al, 2002;Toouli et al, 2002). Likewise, for some strains of lung (MacKenzie et al, 2000;Franco et al, 2001), mammary (O'Hare et al, 2001) and periodontal ligament (Tsutsui et al, 2002) fibroblasts, hTERT-transduced cells required additional mutational events including the loss of p16…”
mentioning
confidence: 99%
“…INK4a pathway is inactivated (Kiyono et al, 1998;Farwell et al, 2000;Kim et al, 2002;Toouli et al, 2002). Likewise, for some strains of lung (MacKenzie et al, 2000;Franco et al, 2001), mammary (O'Hare et al, 2001) and periodontal ligament (Tsutsui et al, 2002) fibroblasts, hTERT-transduced cells required additional mutational events including the loss of p16…”
mentioning
confidence: 99%
“…Transcriptional silencing of p16 INK4a in many immortal cells is due to the hypermethylation of its promoter (Merlo et al, 1995;Serrano, 1997). As shown in Figure 4A, in the CGFR-Ca-1 and -2 cell lines, expression of canine p16 INK4a mRNA was shown to be evidently detectable and was not even altered by treatment with DNA methylation inhibitor, 5-aza-2'-deoxycytidine (5-aza-dC) (Kim et al, 2002b). However, p16 INK4a mRNA was found to be dramatically decreased, while restored in immortal CGFR-Ca-3 Relative cell growth (%)…”
Section: Loss Of P16 Ink4a Regulatory Function In Im M Ortal C Aef Cementioning
confidence: 89%
“…Common genetic alterations frequently observed in the immortalized cells are either associated with the loss of p53 and Rb regulatory functions that are linked with cell-cycle arrest and cell death or the activation of telomerase that maintains telomere integrity or both (Bodnar et al, 1998;Sherr and DePinho, 2000;Kim et al, 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the possibility of establishing immortalized human cell lines in culture. Expression of the catalytic subunit of telomerase (hTERT) could prevent growth arrest and immortalize human fibroblasts and epithelial cells (Morales et al, 1999;Kim et al, 2002b). While these immortalized cells actively proliferated in culture, their growth requirements, cellcycle checkpoints and karyotypic stability were similar to the normal parental cells.…”
Section: Introductionmentioning
confidence: 99%